Impact of Pediatric Obesity on Diurnal Blood Pressure Assessment and Cardiovascular Risk Markers - Murphy, Margaret O.; Huang, Hong; Bauer, John A.; Schadler, Aric; Makhoul, Majd; Clasey, Jody L.; Chishti, Aftab S.; Kiessling, Stefan G. (Frontiers in Pediatrics, 2021)
Background: The prevalence of hypertension is increasing particularly among obese children. Obese children with hypertension are likely to remain hypertensive as they reach adulthood and hypertension is linked to an increased risk for cardiovascular disease. 24-hr ambulatory blood pressure monitoring (ABPM) has become one of the most important tools in diagnosing hypertension in children and circadian patterns of blood pressure may be important disease-risks predictors. Methods: A retrospective chart review was conducted in patients aged 6-21 years who underwent 24-hour ABPM at Kentucky Children’s Hospital (KCH) from August 2012 through June 2017. Exclusion criteria included conditions that could affect blood pressure including chronic kidney disease and other renal abnormalities, congenital heart disease, cancer, and thyroid disease. Subjects were categorized by body mass index into normal (below 85th percentile), overweight (85th -95th percentile), stage I obesity (95th-119th percentile), stage II obesity (120th-139th) and stage III obesity (>140th). Non-dipping was defined as a nocturnal BP reduction of <10%. Results: 263 patients (156 male patients) were included in the analysis, of whom 70 were normal weight, 33 overweight, 55 stage I obesity, 53 stage II, and 52 stage III obesity. Although there was no significant difference between normal weight and obese groups for prevalence of hypertension, there was a greater prevalence of SBP non-dipping in obese patients as BMI increased (p=0.008). Furthermore, non-dippers had a significantly elevated LVMI as well as abnormal lab values for uric acid, blood lipid panel, creatinine, and TSH (p<0.05). Conclusions: These findings demonstrate that obese children constitute a large proportion of hypertensive children and the severity of pediatric obesity is associated with nocturnal BP non-dipping. Additionally, obesity in children is linked to several cardiovascular risk factors including left ventricular hypertrophy, dyslipidemia, and elevated uric acid levels. Further studies utilizing ABPM measures on risk stratification in this very high-risk population are warranted.